Problems of female workers in shops - a social field study- (Damascus University Journal of arts and humanities sciences, 2024)
Women’s work contributes to the comprehensive development process of society, increases family income, and helps the family bear the burden of living with the aim of satisfying some basic needs. This is met with positive, and sometimes negative, results, for many reasons, because her work does not affect her, but rather affects those around her, as a result of her roles. Multiple In this study, we tried to shed light on women’s work in shops in the city of Baghdad, and its most prominent repercussions on them. The aim of this study was to identify the most important social, economic, psychological and health pressures that women face while working in shops, as well as to reveal the motives that lead to women to work in shops, as a random sample of (100) hundred working women was taken from the city of Baghdad, and our study was descriptive and analytical using the socialsurvey approach, and the main study tool was the questionnaire, and the most prominent results that we:1-The worker contributes her salary to meet the family’s needs.         2-The long working hours that working women suffer from .3-Difficulty balancing work and family requirements.4-The adequacy of the monthly salary you receive from your employer.5-Difficulty dealing with customers.6-The female worker may be subjected to harassment and blackmail by the employer.
Keywords: Problems; Work; Shops